PENGARUH PENGGUNAAN KATALIS PADA ELEKTROLISIS AIR GAMBUT DALAM MENGHASILKAN GAS HIDROGEN - Artika, Kurnia Dwi; Musthofa, Imron; Isworo, Hajar; Persada, Anggun Angkasa Bela; Andhika, Muhammad Yusuf; Pamuji, Dian Ridlo (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2025)
Electrolysis is a chemical process in which a substance is broken down into its components using an electric current. The application of electrolysis to peat water has the potential to produce hydrogen and oxygen gas and can change the nature of peat water to make it cleaner and more environmentally friendly. This research aims to determine the productivity of Hydrogen Gas regarding variations in the area of ​​origin of Peat Water with the addition of a baking soda catalyst, as well as to determine the pH of the electrolysis results. The results obtained are that the pH of the peat water will decrease to alkaline around pH 12, and hydrogen production will increase when compared to pure mineral water, where samples of peat water from area B produce around 75% faster than pure mineral water and around 45% faster. when compared to areas A, C, and D.